Radiological features of traumatic vertebral endplate fracture: an analysis of 194 cases with 263 vertebral fractures - Wang, Xiao-Rong; Xu, Fei-Rong; Huang, Qiu-Li; Wáng, Yì Xiáng J. (Chinese medical journal, 2020)
The importance of identifying osteoporotic vertebral endplate or/and cortex fracture (ECF), which primarily includes endplate fracture (EPF) and vertebral anterior cortex buckling, has been recognized. However, some old traumatic ECFs with healing process in the elderly may be mistaken as osteoporotic. This study analyzes the radiological features of traumatic EPF. This was a retrospective analysis of 194 spine trauma patients with 263 vertebral fractures (mean age: 42.11 ± 9.82 years, 118 males and 76 females). All patients had traumatic EPF identified by X-ray/CT/MRI. The involved vertebra was mostly L1 (29.7%), followed by T12 and L2. Except EPFs involved both superior and inferior endplates (12.6%), only 1.9% involved inferior endplate alone, with the majority involved superior endplate. If each endplate was divided into five segments of equal lengths (from anterior to posterior: a1, a2, m, p2, p1), the most depressed point of superior EPFs was mostly at segment-a2 (approximately 45%), followed by segment-a1 (approximately 20%) or segment-m (approximately 20%), and very rarely at segment-p1. The upper 1/3 of anterior vertebral wall was more likely to fracture, followed by middle 1/3 of anterior wall. For posterior vertebral wall fracture, 68.5% broke the bony wall surrounding the basivertebral vain. 58.6%, 30.0%, and 11.4% of vertebral fractures had <1/5, 1/5-1/3, and >1/3 vertebral body height loss. As the extent of vertebral height loss increased, the chance of having both superior and inferior EPFs also increased; however, the chance of having inferior EPF alone did not increase. Traumatic EPF features are characterized, which may help the differentiation of traumatic and osteoporotic EPFs.